How do zero-coupon inflation swaps predict inflation rates in the euro area? Evidence of efficiency and accuracy on 1-year contracts - Ribeiro, P. P.; Curto, J. D. (Empirical Economics, 2017)
This paper examines the risk-neutral efficient market hypothesis for inflation swap markets in the euro area from 2005.10 to 2014.07. Overall, we conclude that 1-year zero-coupon inflation swap rates are unbiased predictors of inflation rates. Further, there is no empirical evidence of an inflation risk premium and the assumption of rationality seems to hold. Definitely, these inferences encourage the reading of inflation expectations embedded in short-term inflation swaps. Additionally, we compare the predictive ability of inflation swaps with other measures of inflation expectations. The in-sample results show that, in contrast with surveys, market-based measures are able to accurately forecast inflation rates. In turn, based on an out-of-sample analysis, a straightforward econometric model dominates other sources. Therefore, a combined analysis that uses different sources contributes to a more robust view of future inflation rates.